Rancang Bangun Low Clearance Split Frame (LCSF) Untuk Pemotongan Casing Maerial Baja Karbon - Doni Suseno (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Cutting metals, such as carbon steel, is a stage of engineering and repairing casing pipes or casings made of carbon steel material in accordance with the cut marks that have been set in the marking process. For pipe cutting or welding preparation tasks related to maintenance or new construction, there are basically two different methods used. The first is hot cutting by hand grinding, and the second is a portable unit popularly known as cold cutting that produces weld-ready surfaces. Low Clearance Split Frame (LCSF) is a portable unit used as cold cutting that produces weld-ready surfaces, where cutting occurs due to an air pressure reaction from the water compressor with a portable unit and carbon steel. Low Clearance Split Frame (LCSF) is used manually without going through a heating process, where the unit is mounted around the outer diameter of the case in parallel or tucked into an open-end pipe, and is designed to apply square and precision cuts. The unit requires little maintenance in the form of lubrication, fast operating time and no hot work. For the cutting work here, the material used is a carbon steel casing. In the cutting work of carbon steel casings here, Low Clearance Split Frame (LCSF) is used, where the obstacles found are found in the cutting blade or called the parting blade that is dull, so that sometimes the results of the cutting work become inefficient, such as the surface of the casing that is not smooth and the time to finish the work. This causes the process of sharpening or replacing the parting blade, until the machine can operate optimally. As of this writing, it has been designed for cutting carbon steel casings using Low Clearance Split Frame (LCSF) which aims to produce straight, flat and smooth cuts of carbon steel casings and can produce a 20